ANALISIS TERHADAP PERHITUNGAN PAJAK PENGHASILAN PASAL 29 PT NTV TAHUN 2020 - Grisheilla Muliana; Purnamawati Helen Widjaja (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study is to determine whether the fiscal corrections made by the company are in accordance with Financial Accounting Standards (SAK) and tax regulations as well as the amount of underpayment of income tax payable. The object of this research is PT NTV, a company engaged in bags and luggage. The methods used are qualitative and quantitative methods. With data collection methods using interviews, documentation, and literature study. The results of this study indicate thatthere are differences in the corrections made by PT NTV so that the underpayment of taxes or Income Tax Article 29 of the company becomes different.